Developing Spinning Wheel Game to Teach Speaking Skills for Senior High School Students - Lestari, Fira Ayu; Widiarini; Makrifah, Istina Atul (PROJECT (Professional Journal of English Education), 2025)
The purpose of this research is to develop spinning wheel game as a learning media to teach English speaking skill. Physical spinning wheels enhance learning by boosting student motivation through interactive and tactile engagement. This study uses the Research and Development (R&D) method by applying the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation in developing learning media. Qualitative data were collected from unstructured interviews with English teachers and validator feedback on the Spinning Wheel game. Quantitative data were collected through questionnaires using a Likert scale for validation of instruments, media, materials, and student satisfaction. The instrument expert obtained 90%, the media expert 92%, and the lesson expert 78%, all categorized as "Valid." Student satisfaction reached 81.25%, falling under the "Very Feasible" category. In conclusion, the Spinning Wheel Game effectively can be used to teach tenth grade students' English speaking skills through interactive and engaging learning.